1984
DOI: 10.1029/rs019i002p00578
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic consequences of Papadopoulos' discharge model of spacecraft ram glows

Abstract: The gaseous and surface impact‐excited ultraviolet, visible, and infrared emissions that would result from plasma interactions near the windward directed surfaces of satellites orbiting in the earth's F region are reviewed. No process in the electrical discharge that would produce the intense orange‐red component of the glows seen on space shuttle and Atmospheric Explorer vehicles is identified. Spectroscopic and spatial‐distribution measurements to determine the contribution to the excitation of the collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Papadopoulos [1984] proposed an alternate theory of the Space Shuttle surface glows in terms of a plasma discharge mechanism producing suprathermal electrons and ions which excite the species in the shuttle environment. The spectroscopic consequences of this model seem to indicate that such a mechanism cannot be responsible for the observed glow [Kofsky, 1984]. Furthermore, no dependence of the glow intensity on the ambient plasma density was found by Yee et al [1984] when analyzing photometric data from the visible airglow experiment on board the Atmosphere Explorer satellite.…”
Section: Local Contaminationmentioning
confidence: 88%
“…Papadopoulos [1984] proposed an alternate theory of the Space Shuttle surface glows in terms of a plasma discharge mechanism producing suprathermal electrons and ions which excite the species in the shuttle environment. The spectroscopic consequences of this model seem to indicate that such a mechanism cannot be responsible for the observed glow [Kofsky, 1984]. Furthermore, no dependence of the glow intensity on the ambient plasma density was found by Yee et al [1984] when analyzing photometric data from the visible airglow experiment on board the Atmosphere Explorer satellite.…”
Section: Local Contaminationmentioning
confidence: 88%
“…Currently, three mechanisms have been proposed as the cause of surface glow [218][219][220][221][222][223]. The first is an atomic oxygen reaction, since glow seems to correlate with the atomic oxygen environment.…”
Section: Discussion Of Interactionmentioning
confidence: 99%
“…In an early qualitative analysis of the shuttle glow, found that the intensity e-fold fall-off distance from the surface was between 5 m to 10 an. A more detailed analysis has shown that this radiative decay length is closer to 20 m (Yee and Dalgarno, 1983) although their appears to be a secondary contribution having an e-fold distance of about I m (Slanger, 1983;Swenson et al, 1986a).…”
Section: Introductionmentioning
confidence: 96%